Analisis Pengendalian Internal Persediaan Berbasis COSO dalam Mengendalikan Risiko Operasional (Studi Kasus PT Mestika Makmur Persada Jaya) - Intan Adelia; Muhammad Lathief Ilhamy Nasution; Nur Ahmadi Bi Rahmani (Jurnal Sistem Informasi Akuntansi, 2026)
This study aims to analyze the implementation of the internal control system for inventory at PT Mestika Makmur Persada Jaya based on the COSO framework and to examine its role in controlling operational risks. This study employs a qualitative descriptive approach using the case study method. Data were collected through interviews, observations, and documentation of informants involved in inventory management. Data analysis was conducted interactively through the stages of data reduction, data presentation, and drawing conclusions. To support the qualitative analysis, a percentage-based measurement was applied as a complementary tool to assess the effectiveness level of the internal control system. The results of the study indicate that all components of the COSO framework such as the control environment, risk assessment, control activities, information and communication, and monitoring have been effectively implemented, with an overall effectiveness of 93.33%. The internal control system effectively mitigates operational risks, including stock discrepancies, inventory damage, loss, and shipment errors. These findings demonstrate that a structured internal control system not only ensures reliable inventory information but also enhances operational efficiency. The study contributes both practically by providing recommendations to improve inventory management and academically by supporting the development of managerial accounting and internal audit practices.